A simple effective duty cycle controller for high power factor boost rectifier - Athab, Hussain S.; Khan, P. K. Shadhu (2007)
This paper proposes a simple low-cost modulating duty cycle analog controller to reduce line harmonies for high power factor boost rectifier. The proposed method eliminates the need for current sensing, and simultaneously offers the performance results comparable to those of continuous conduction mode (CCM) scheme. This scheme also maintains the simplicity comparable to that of discontinuous conduction (DCM). Only the output voltage and the rectified input voltage are monitored to vary the duty cycle of the boost switch within a line cycle so that the third-order harmonic, which is the lowest order harmonic (LOH) of the input current, is reduced. As a result, the total harmonic distortion (TBD) of the line current as well as the input power factor is improved. The proposed method is developed for constant switching frequency boost rectifier. Simulation and experimental results are presented to verify the effectiveness of the proposed control method.